Podoba Primoža Trubarja v slovenski esejistiki - Bergles, Katja (Slavia Centralis, 2020)
Primož Trubar’s Image in Slovene EssayisticThis paper presents an overview of the selected essay corpus of Ivan Cankar, Taras Kermauner, Ferdo Kozak, Denis Poniž, Ivan Prijatelj, Alojz Rebula, and Jože Snoj. In their texts I attempted to find confirmation of the thesis of Ivan Prijatelj that the consciousness of ourselves, and of the fact that Slovene culture and the Slovene national essence took shape in relatively close and positive connection with German culture, was decisively formed by Trubar and by the Slovene Reformation.
Keywords: Trubar; Protestantism; the Essay; Cankar